2015
DOI: 10.1055/s-0035-1554926
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Graft Isometry Is Affected by the Orientation of the Femoral Tunnel

Abstract: ACL graft length and tension change throughout knee range of motion and also depend on femoral tunnel orientation and fixation type. The use of an all-epiphyseal tunnel with suspensory fixation should be studied further for evidence of graft elongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…It is possible the small differences in deep-shallow femoral aperture position and/or femoral tunnel obliquity between these 2 techniques may have explained some of the differences, as other authors have suggested. 12 We also feel it is possible that factors unrelated to either technique played a role in the anisometry data. One potential explanation for the difference in graft-length change between HTT and AM portal knees is that grafts may have tended to occupy slightly different locations within the respective tunnels for these 2 techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible the small differences in deep-shallow femoral aperture position and/or femoral tunnel obliquity between these 2 techniques may have explained some of the differences, as other authors have suggested. 12 We also feel it is possible that factors unrelated to either technique played a role in the anisometry data. One potential explanation for the difference in graft-length change between HTT and AM portal knees is that grafts may have tended to occupy slightly different locations within the respective tunnels for these 2 techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It is not yet clear that the degree of graft-tunnel angulation seen with AM portal reconstructions has any implications for graft survival in a clinical setting, although the effect of femoral tunnel orientation has recently been recognized as significant biomechanically. Ebersole et al 12 demonstrated in a cadaveric model that, with the same anatomic femoral tunnel aperture, the increased femoral tunnel angulation associated with an all-epiphyseal technique tripled graft strain relative to TT and AM constructs. Further study is needed to determine if lesser degrees of femoral tunnel obliquity affect graft survival and/or performance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that the magnitude of the graft bending angle seen with AM portal tunnels results in a 2- to 3-fold increase in graft strain at the femoral tunnel aperture, producing increased graft signaling on postoperative magnetic resonance imaging. 12,21,34,35…”
Section: Discussionmentioning
confidence: 99%
“…This makes graft passage more tedious, increases graft forces at the tunnel aperture, and may negatively affect graft healing. 5,12,34,35…”
mentioning
confidence: 99%
See 1 more Smart Citation